Pengembangan Modul Biologi Berbasis Potensi Lokal Kabupaten Enrekang pada Materi Plantae untuk Siswa Kelas X SMA - Hasmiati Hasmiati; Musma Rukmana; Fernando Andre Watung; Tika Putri Agustina (Jurnal Biotek, 2023)
Nature has enormous potential to aid in the study of biology. This potential can be effectively harnessed when presented in teaching materials, such as modules. This research aimed to produce valid learning modules based on the local potential found in Enrekang Regency, which can facilitate contextual and meaningful biology learning. The research method employed was Research and Development (R&D), utilizing the ADDIE development model. Data was collected using an expert validation sheet to assess the module's validity in terms of content, language, presentation, and appearance. The Plantae module, as a product of this development, is based on the local potential and exhibits characteristics such as being self-instructional, self-contained, stand-alone, adaptable, user-friendly, and including pictures of local plants from Enrekang Regency. Based on data analysis, the developed module fulfills the validity criteria in all aspects of the assessment, with an average validity score of 4.1. Consequently, the research concludes that the developed module is valid and can effectively support biology learning by incorporating the local potential of Enrekang Regency.